2011
DOI: 10.1371/journal.pone.0017347
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Reference Genes across Physiological States for qRT-PCR through Microarray Meta-Analysis

Abstract: BackgroundThe accuracy of quantitative real-time PCR (qRT-PCR) is highly dependent on reliable reference gene(s). Some housekeeping genes which are commonly used for normalization are widely recognized as inappropriate in many experimental conditions. This study aimed to identify reference genes for clinical studies through microarray meta-analysis of human clinical samples.Methodology/Principal FindingsAfter uniform data preprocessing and data quality control, 4,804 Affymetrix HU-133A arrays performed by clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 58 publications
3
51
0
Order By: Relevance
“…Three of our six successfully screened genes belong to this family, and many genes in this set have been verified in other studies to be suitable reference genes [23][24][25]. We also found that the expression levels of certain ribosome protein-encoding genes, such as ribosomal protein S7 (RPS7), ribosomal protein S10 (RPS10), RPLP0, and ribosomal protein L21 (RPL21) varied widely, ranging from single digits to tens of thousands of RPKM value.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Three of our six successfully screened genes belong to this family, and many genes in this set have been verified in other studies to be suitable reference genes [23][24][25]. We also found that the expression levels of certain ribosome protein-encoding genes, such as ribosomal protein S7 (RPS7), ribosomal protein S10 (RPS10), RPLP0, and ribosomal protein L21 (RPL21) varied widely, ranging from single digits to tens of thousands of RPKM value.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, the expression of GAPDH has been reported to be upregulated in many other disorders such as inflammation, diabetes, hypoxia, and some respiratory diseases, suggesting that it should only be cautiously used as a reference gene in studies of these diseases [36 -40]. Indeed, in a large-scale microarray metaanalysis, GAPDH was not recommended as a reference gene, except in heart or muscle [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common shortcoming of many previous attempts is that tissue specificity of the genes was reported [102][103][104][105][106][107][108][109][110][111][112], or avoided [113][114][115]. However, no attempts were made to actually use such data for quality control or evaluation of the expression data, or if they were, it was for cancer analysis within one tissue [116][117][118] or to study the expression of synonymous codons in plants [119].…”
Section: Existing Expression Data Quality Control Methods and Their Amentioning
confidence: 99%
“…An integrative data analysis, a so-called meta-analysis, can serve as a remedy by combining information from independent but related studies in order to enhance the statistical power, reliability, and generalizability of results (Normand 1999;Ramasamy et al 2008). In addition to refining and validating hypotheses between analogous studies (Arasappan et al 2011;Griffith et al 2006;Grutzmann et al 2005;LaCroix-Fralish et al 2011;Parmigiani et al 2004;Rhodes et al 2002;Shen et al 2004;Smith et al 2008;Vierlinger et al 2011;Wang et al 2004), metaanalyses can be used to identify a meta-signature across related studies (Anders et al 2011;Daves et al 2011;Pihur et al 2008;Rhodes et al 2004); to address novel questions Cheng et al 2011;Wennmalm et al 2005); and/ or to infer co-expression patterns and gene function (Lee et al 2004;Stuart et al 2003;Wren 2009;Zhou et al 2005). Ultimately, metaanalyses can provide the opportunity to maximize the use of available data to help to uncover underlying biological mechanisms.…”
Section: Introductionmentioning
confidence: 99%